Hubungan Dukungan Keluarga Dalam Program Prolanis Dengan Kepatuhan Minum Obat Pasien Diabetes Melitus Tipe 2 Di Puskesmas Rawat Inap Banjarsari Kota Metro Tahun 2019 - Vio Nita Gustianto; Muhammad Djakfar Sadiq (JIKMI (Jurnal Ilmu Kesehatan Masyarakat Indonesia), 2020)
AbstractDiabetes mellitus is a chronic metabolic disorder due to the pancreas not producing enough insulin or the body cannot use insulin produced effectively. Metro City ranks 1 in Lampung Province with the number of people with diabetes mellitus. Banjarsari Public Health Center in Metro City has a Prolanis program with 50 people with type 2 diabetes mellitus but only 16 people with type 2 diabetes who measure blood sugar levels with the results of 5 people (31.25%) blood sugar levels> normal and 11 people (68.75 %) blood sugar levels in the normal category. This study uses a cross sectional design from 26 to 31 July 2019 at Banjarsari Community Health Center in Metro City in 2019. The sample of this study was 45 respondents. Data analysis using univariate and bivariate. For bivariate use the chi-test test. The results showed that there was a significant relationship between family involvement in the prolanis program (p value of 0.039) with adherence to take medication for Type 2 Diabetes Mellitus patients at the Banjarsari Community Health Center in Metro City in 2019. From the results of the study it was suggested to be able to invite and include families of people with diabetes mellitus type 2 in providing health care and for people with type 2 diabetes mellitus in order to foster self-awareness to change healthy lifestyles.Keywords  : Family Involvement, Patient Drug Adherence ComplianceAbstractDiabetes mellitus is a chronic metabolic disorder due to the pancreas not producing enough insulin or the body cannot use insulin produced effectively. Metro City ranks 1 in Lampung Province with the number of people with diabetes mellitus. Banjarsari Public Health Center in Metro City has a Prolanis program with 50 people with type 2 diabetes mellitus but only 16 people with type 2 diabetes who measure blood sugar levels with the results of 5 people (31.25%) blood sugar levels> normal and 11 people (68.75 %) blood sugar levels in the normal category. This study uses a cross sectional design from 26 to 31 July 2019 at Banjarsari Community Health Center in Metro City in 2019. The sample of this study was 45 respondents. Data analysis using univariate and bivariate. For bivariate use the chi-test test. The results showed that there was a significant relationship between family involvement in the prolanis program (p value of 0.039) with adherence to take medication for Type 2 Diabetes Mellitus patients at the Banjarsari Community Health Center in Metro City in 2019. From the results of the study it was suggested to be able to invite and include families of people with diabetes mellitus type 2 in providing health care and for people with type 2 diabetes mellitus in order to foster self-awareness to change healthy lifestyles..Keywords  : Family Involvement, Patient Drug Adherence Compliance